Field Emission from Lateral Multiwalled Carbon Nanotube Yarn Emitters - Chen, Guohai; Song, Yenan (Frontiers in Materials, 2016)
A field emission from a lateral emitter made by a multiwalled carbon nanotube (MWCNT) yarn was investigated. The lateral emitter showed an excellent field emission performance with a low turn-on electric field of 1.13 V/um at an emission current of 1 uA, high emission current of 0.2 mA at an applied voltage of 700 V, and long-time emission stability for over 20 h without any significant current decay under an initial emission current of about 0.10 mA. The lateral emitter also demonstrated a uniform line emission pattern. It is suggested that the field emission occurs from the outmost MWCNTs which are protruding out from the yarn surface.